Strategic management of non-Olympic sports (on the example of Sumo). - Anastasia Bondar; Bairamov Ruslan (Kharkiv State Academy of Physical Culture, 2019)
Purpose: to determine Sumo's development strategy in Kharkiv region. Material and methods: the Statute of the public organization "Kharkiv Regional Sumo Federation" and the National Strategy for Healthy Movement Activity in Ukraine for the Period up to 2025 "Motor Activity - Healthy Lifestyle - Healthy Nation" (2016) are analyzed, systematic analysis and modeling method made it possible to build a strategic model of sumo development in Kharkiv region, a sociological survey among the residents of Kharkiv region helped to determine the opinion of Sumo population and its prospects in our region, the method of expert assessments was used to evaluate the prospective sumo development plan developed during the study in the Kharkov region. Results: The results obtained complement and extend current scientific data on the strategic management of the development of non- Olympic sports in Ukraine. The outlined plan reveals a network of activities that underpin the model and will contribute to the strategic development of Sumo in the region. For effective implementation of the perspective plan we propose to the NGO "Kharkiv Regional Sumo Federation" to create a structural subdivision "Sumo Development Center" with the status of a Legal Entity, to carry out its own economic activity, which is stipulated by the Federation statute and does not contradict the current legislation, which entrust the duties of external relations and marketing. On the basis of the Center to create structural units that will meet the specific areas of work: "Sports Complex", "Sumo Academy", "Sumo Museum", "Sport Shop", "Marketing Department", "Publishing House" (or publishing department). Our strategic model, taking into account internal and external risks, reflects the development of non- Olympic sports, in particular sumo, effective management will contribute to the solution of urgent tasks at each stage and the achievement of the general goal. Conclusions: the results complement and expand the current scientific data on the development of non- Olympic sport, development of sumo, methods of teaching sumo. The research determines the development of the sumo in the Kharkiv region, the structure, directions of activity of the public organization of sporting-sports direction of the Kharkiv Regional Sumo Federation in accordance with the Charter. Polls of ordinary citizens showed that, in the opinion of most of them, the Federation should intensify its marketing activities, increase the number of TV broadcasts, create official websites of federations and clubs on the Internet. Experts' opinions confirm the opinion of citizens, the greatest opportunities for the further development of the federation opens the popularization of the sumo among the population and the expansion of the range of services of the federation itself, improving quality and advertising of their own services, as well as legislative changes. In the opinion of ordinary citizens and experts estimate, the state has the least impact on the development of sumo in our Region and on the activities of the Federation.